Chemical vapor infiltration of additively manufactured preforms: Pore‐resolved simulations and experimental validation. Issue 4 (9th December 2021) - Ramanuj, Vimal; Sankaran, Ramanan; Jolly, Brian; Schumacher, Austin; Mitchell, David
Abstract: The densification of additively manufactured porous preforms by chemical vapor infiltration (CVI) is studied using pore‐resolved simulations and experiments. Experimentally, 3D printed silicon carbide (SiC) preforms are subject to CVI synthesis using methyltrichlorosilane (MTS) precursor to obtain high purity SiC/SiC composites. Optical images of the cross sections of the processed preforms are analyzed to obtain the spatial porosity distribution. The numerical method is based on a level set formulation to capture the spatial distribution and time evolution of the pore scale microstructural characteristics. The coupled transport and kinetic effects are represented using a dimensionless Thiele modulus. Simulations are initialized using representative synthetic preform geometries comprising of packed particles based on the size distribution of the powder used for 3D printing. The simulation results are validated against the experimental observations in terms of total density and the distribution of residual porosity. The densification characteristics, porosity classification, concentration profiles, and structure functions are analyzed as functions of processing temperature and Thiele modulus.